AP‐3 complex subunit delta gene, ap3d1, regulates melanogenesis and melanophore survival via autophagy in zebrafish (Danio rerio). (29th August 2022) - Neuffer, Sam J.; Beltran‐Cardona, David; Jimenez‐Perez, Kevin; Clancey, Lauren F.; Brown, Alexander; New, Leslie; Cooper, Cynthia D.
Abstract: Zebrafish are an emerging model organism to study the syndromic albinism disorder, Hermansky–Pudlak syndrome (HPS), due to visible pigment development at 24 hours postfertilization, and conserved melanogenesis mechanisms. We describe crasher, a novel HPS type 10 (HPS10) zebrafish model, with a mutation in AP‐3 complex subunit delta gene, ap3d1 . Exon 14 of ap3d1 is overexpressed in crasher mutants, while the expression of ap3d1 as a whole is reduced . ap3d1 knockout in *AB zebrafish recapitulates the mutant crasher phenotype. We show ap3d1 loss‐of‐function mutations cause significant expression changes in the melanogenesis genes, dopachrome tautomerase ( dct ) and tyrosinase‐related protein 1b ( tyrp1b ), but not tyrosinase ( tyr ). Last, Generally Applicable Gene‐set Enrichment (GAGE) analysis suggests autophagy pathway genes are upregulated together in crasher. Treatment with autophagy‐inhibitor, bafilomycin A1, significantly decreases melanophore number in crasher, suggesting ap3d1 promotes melanophore survival by limiting excessive autophagy. crasher is a valuable model to explore the regulation of melanogenesis gene expression and pigmentation disease.